Lebbeus dentatus n. sp. (Decapoda, Thoridae) described from a seamount of the Caroline Plate, NW Pacific - Wang, Yan-Rong; Sha, Zhong-Li (Zootaxa, 2024)
Based on the female specimen collected from an unnamed seamount on the Caroline Plate in the NW Pacific, a new species of the thorid genus Lebbeus White, 1847, L. dentatus n. sp., is described and illustrated. The new species belongs to a species group characterized by the possession of epipods on the pereopods 1 and 2, but is characteristic in the carapace having a strong supraorbital tooth extending to 0.3 length of the rostrum and largely unarmed dorsal margin of the rostrum. Integrative approach using morphological comparison and genetic analyses with the mitochondrial COI and 16S rRNA genes is taken to clarify the specific identities of the new taxon. An identification key to species belonging to the species group of Lebbeus characterized by the possession of epipods on the pereopods 1 and 2 is presented.